THE RELATIONSHIP BETWEEN STUDENTS’ LANGUAGE LEARNING STRATEGIES AND THEIR THINKING STYLES USE - Nasukhah Nasukhah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract: Many students feel difficult in learning English so that makes them very lazy and they are not interested in English. To be able to understand English easily, students have to employ the appropriate learning strategy and thinking style. Therefore, this study focuses on language learning strategies and thinking styles. Both of them are very helpful for beginner or students. This study aimed to find out what is the most language learning strategies and thinking styles that are usually applied by students when they are in learning process and to find out the relationship between language learning strategies and thinking styles. This study used quantitative method. The researcher took students of the eleventh graders of MA Almaarif Singosari. The linguistic major students as the participants consisting of 47 students from two classes. Questionnaire is the instrument of this study. To analyze the data, the researcher used SPSS version 20. The finding of the study indicated that metacognitive strategy is type of strategy mostly used at mean point 5.97 and executive style is  mostly applied by students at mean point 3.78. There is a correlation between language learning strategies and thinking styles at significant value .001. It can be summed up that metacognitive is the dominant strategy and executive is the style the most used by students and also there is a relationship between language learning strategies and thinking styles. Keywords: Language Learning Strategies, Thinking Styles